The Impact Of The Decline In Oil Prices On The Performance Of The Iraqi Market For Securities - Hlail Srayyih, Faez; Howaidi, Omar; Battal Hussain, Ahmad (Opción, 2019)
The primary source of oil-producing countries, which depend primarily on their economy for oil, is that their economies are linked to the global economy. These countries are greatly affected by the changes in the world oil prices, the fluctuations of oil prices directly affect all indicators of the global economy, that high oil prices will lead to the growth of exports of the producing coun- tries, and thus increase government spending, and vice versa will be in the event of declining world oil prices will be reflected negatively On the economic and social situation in the oil producing countries.Iraq is among the oil-ex- porting countries, and its economy depends entirely on oil, and the impact of the decline in global oil prices will lead to the deterioration of Iraqi share- holding companies, which leads to a decrease in profitability and liquidity as well as some other financial factors, and the current study will shed light on the impact of the global oil price decline on Indicators and general financial factors in the market, the current study aims to know the effect of low oil prices on financial indicators, the current study is divided into multiple axes, theoretical concepts of oil prices will be presented, and economic effects in the case of low oil prices, analysis of decline Oil prices on the indicators of the Iraq Stock Exchange. Among the most prominent findings of the study to the existence of a relationship between low oil prices and indicators of the Iraqi market for securities.